2018
DOI: 10.4172/2375-4427.1000182
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Captioning and Sign Language in Understanding Television Content in Deaf

Abstract: Objectives: The aim of the present study was to evaluate the benefits of combined use of captions and sign language interpretation in understanding television content. Methods: 30 prelingually deaf adults (25-45 y) participated in the study. Stimulus consisted of three video-clips taken from Television (TV) program "Shaktimaan" with already incorporated sign language video. Captions were incorporated in two of the video clips. The experiment was conducted in three phases. In pre-experimental phase participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…Participants' perceived quality of sign language interpretation is linked to stage lighting, use of non-transparent facemask and unprofessionalism of cameramen. This observation is congruence to studies, which had earlier reported some challenges, faced by persons who are deaf when assessing sign language interpretation via the television [24][25][26]28]. Kyle and Allsop [24] and Stone [26] noted that the deaf television audience may have difficulties, following sign language interpretation when cameras and illumination, focused on SLIs, are not adequate.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Participants' perceived quality of sign language interpretation is linked to stage lighting, use of non-transparent facemask and unprofessionalism of cameramen. This observation is congruence to studies, which had earlier reported some challenges, faced by persons who are deaf when assessing sign language interpretation via the television [24][25][26]28]. Kyle and Allsop [24] and Stone [26] noted that the deaf television audience may have difficulties, following sign language interpretation when cameras and illumination, focused on SLIs, are not adequate.…”
Section: Discussionsupporting
confidence: 87%
“…In their studies, Chiaro and Nocella [34] as well as Po¨chhacker [35] note that colour contrast is a major factor that informs the decision of the deaf audience to watching interpreted televised programmes. Chiaro and Nocella [25] specifically identified backdrop colour in an interpreters' frame (picture-in-picture) as the major determinant of quality sign language interpretation and acceptance by the deaf audience.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations